Evaluations of Intervention Program on Nurses` Practices about Care of Children with Diabetic Ketoacidosis - Turkey, Firas; Ajil, Zaid W. (Iraqi National Journal of Nursing Specialties, 2023)
Objective(s): To evaluate of intervention program on nurses’ practices about care of children with diabetic's ketoacidosis. Methodology: A quasi-experimental design that applied at teaching hospitals for pediatric in AL Ramadi city to establish the Effectiveness of Intervention Program on Nurses` Practices about Care of Children with Diabetic Ketoacidosis from 3th of March 2022 till 20 of March 2023. Non-probability (purposive) sample of (50), likewise was alienated into the study (experimental) group. The study group included (50) nurses non-randomly selected from AL-Ramadi Teaching Hospital.A preliminary study has conducted in AL-Ramadi Teaching Hospital The whole number of nurses was (20) for 4 days, by using questions of the open-ended answers. The validity of the questionnaire and educational program are tested by (25) experts from related fields.Results: Reliability of survey and program tried through a pilot investigation of It included (10) medical caretakers, non-randomly selected from AL-Ramadi Teaching Hospital (this sample was excluded from the original study sample) by using test-retest technique and Cronbach's Alpha measurement, the results for practice was (0.933).The study findings have proved the effectiveness of the program through high percent obtained between the pre-test and post-test1 and post-test 2. It was sample study group results in pre-test is 31.76% (19) with regard to them on a not acceptable level, but post-test 1 is 77.04% (26) through esteem to them on a good level, and also post-test 2 remains 80.98% (24) with esteem to them on a good level.Conclusions: The study concluded that the intervention program has significant effect on nurses practice about diabetic's ketoacidosis. It is improving nurses practice from poor to good practice after implementation of the intervention program.Recommendations: the study has recommended that training courses and workshops for nurses of the hospital teaching of pediatric regarding Diabetics Ketoacidosis care, increasing nurses' numbers especially those who hold nursing Bachelor's degrees to work at pediatric teaching hospitals for their ability and background.